Trace Elements Analysis by ICP-OES after Microwave Digestion of Medicago sativa L. Seeds from Different Locations in Xinjiang, China - Liu, Feng; Liu, Wenxian; Ding, Wenhuan; Lv, Guangyao; Zhou, Xiaoying (Asian Journal of Chemistry, 2014)
The concentration of twelve trace elements (Ca, Cd, Cr, Cu, Fe, Hg, K, Mg, Mn, Na, Pb, Zn) in eight Medicago sativa L. seeds samples, which were uygur medicine and carried out by inductively coupled plasma optical emission spectrometry (ICP-OES). A diluted oxidant mixture (2 mL HNO3 + 1 mL H2O2 + 3 mL H2O) was used to achieve the complete decomposition of the organic matrix in a closed-vessel microwave oven. The accuracy of the entire proposed method was confirmed by standard reference material analysis. Twelve trace elements contents were found detected at in different Medicago sativa L. seeds samples. The results in the samples (minimum-maximum in μg/g) were : Ca 0.022-0.058, Cr 0.126-7.106, Cu 0.570-4.504, Fe 8.004-12.588, Mn 0.035-0.054, Ni 0.908-2.182, Pb 0.099-0.134 and Zn 2.206-8.982, respectively. The trace elements analysis method of the ICP-OES was found to be fast, reliable, simple and excellent in determination of the trace elements.